Role of Ulipristal Acetate in Treatment of Fibroid: A Prospective Study - Behl, Pooja; Warman, Shalini; Saha, Madhulima; Shanker, Ojasvi (International Journal of Innovative Research in Medical Science, 2025)
Background: Uterine fibroids are the most common benign tumours in women of reproductive age group which may present with heavy menstrual bleeding, dysmenorrhea, pelvic pressure and anaemia. Its management depends on the number, size and location of the ﬁbroids, patient’s age and desire to preserve fertility. Ulipristal acetate (UPA) is a selective progesterone receptor modulator which selectively inhibits the proliferation of uterine leiomyoma cells and induces their apoptosis. Objectives: The objective of the study was to evaluate the efficacy of ulipristal acetate in reducing the size of a symptomatic fibroid, its effect on menstrual bleeding, dysmenorrhea and its side effects. Materials and methods: A total of 45 patients were included in this prospective study. Oral ulipristal acetate at a dose of 5 mg per day was given for a period of 3 months. The PBAC Score, Visual Analogue Scale score and ultrasound findings of fibroid were noted. Results: Ulipristal acetate is an effective drug in reducing heavy menstrual bleeding, pain and fibroid size with minor side effects. Conclusion: Ulipristal acetate can be a safe, effective and economic option for treatment of symptomatic fibroids in patients.